Baclofen and the Alcohol Withdrawal Syndrome-A Short Review - Cooney, Gary; Heydtmann, Mathis; Smith, Iain D. (Frontiers in Psychiatry, 2019)
The Alcohol Withdrawal Syndrome (AWS), which may occur with or without delirium, is a frequent consequence of sudden alcohol cessation in patients with moderate to severe Alcohol Dependence Syndrome (ADS). Withdrawal as a result of habituation to alcohol is part of the definition of the Alcohol Dependence Syndrome (ICD10). Since the recognition of Delirium Tremens, in the early nineteenth century, the management of the syndrome, an acute medical emergency, has proven controversial. The barbiturates , chlormethiazole and recently the safer benzodiazepines transformed the management of these conditions. The benzodiazepines , particularly diazepam and chlordiazepoxide, are now the most used first line agents in the treatment of AWS. In addition, a number of other agents , including baclofen, a GABA-B receptor agonist, have the potential to suppress the alcohol withdrawal syndrome. In this review we review the potential use of baclofen in its role to treat AWS. We summarise initial case reports as well as more recent randomized trials of AWS treatment with baclofen. We conclude that currently there is not enough evidence to support the use of baclofen as a first line treatment for AWS. More research will be needed to determine where baclofen might have a role in second-line management of the Alcohol Withdrawal Syndrome on its own or in combination with benzodiazepines or other agents.